2022
DOI: 10.3389/fcvm.2021.809689
|View full text |Cite
|
Sign up to set email alerts
|

Rutaecarpine Inhibits Doxorubicin-Induced Oxidative Stress and Apoptosis by Activating AKT Signaling Pathway

Abstract: Patients with cancer who receive doxorubicin (DOX) treatment can experience cardiac dysfunction, which can finally develop into heart failure. Oxidative stress is considered the most important mechanism for DOX-mediated cardiotoxicity. Rutaecarpine (Rut), a quinazolinocarboline alkaloid extracted from Evodia rutaecarpa was shown to have a protective effect on cardiac disease. The purpose of this study is to investigate the role of Rut in DOX-induced cardiotoxicity and explore the underlying mechanism. Intraven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
(40 reference statements)
0
8
0
Order By: Relevance
“…[ 38 ] Rutaecarpine (Rut), a quinazolinocarboline alkaloid extracted from Wuzhuyu was shown that it could ameliorate oxidative stress by improving SOD and glutathione (GSH), while inhibiting malondialdehyde (MDA). [ 39 ] Niu et al [ 40 ] showed that Chinese herbs Guizhi could improve oxidative stress induced by Chinese herbs Mahuang ( Ephedra sinica Stapf ). The steroidal saponins extract from Maidong and ingredients of Shengjiang have been proved to have antiinflammatory and antioxidant effects.…”
Section: Discussionmentioning
confidence: 99%
“…[ 38 ] Rutaecarpine (Rut), a quinazolinocarboline alkaloid extracted from Wuzhuyu was shown that it could ameliorate oxidative stress by improving SOD and glutathione (GSH), while inhibiting malondialdehyde (MDA). [ 39 ] Niu et al [ 40 ] showed that Chinese herbs Guizhi could improve oxidative stress induced by Chinese herbs Mahuang ( Ephedra sinica Stapf ). The steroidal saponins extract from Maidong and ingredients of Shengjiang have been proved to have antiinflammatory and antioxidant effects.…”
Section: Discussionmentioning
confidence: 99%
“…Nrf2 has long been recognised as an antioxidant and has a very high antioxidant capacity [16].DOX induces oxidative stress in cardiomyocytes by inhibiting the SIRT1/LKB1/AMPK/Nrf2 signalling pathway, HSP20/AKT/GSK3β/FYN/Nrf2 signalling pathway [17,18];inhibits autophagy by suppressing Nrf2 expression [19]; and induces cardiomyocyte apoptosis by inhibiting upstream of the PI3K / AKT signalling pathway and P38/MAPK to induce cardiomyocyte apoptosis [20,21]; and inducing iron death in cardiomyocytes by regulating the expression of p62 and thereby inhibiting the expression of Nrf2 [22], and SIRT1 may be one of the key components in the inhibition of Nrf2-induced iron death by DOX.The SIRT3/Nrf2 signalling pathway is involved in Doxorubicin-induced cardiomyocyte pyroptosis [23], and inhibition of the PI3K/AKT/Nrf2/p38/NF-κB p65 axis may be related to the pathway of Doxorubicin-induced cardiomyocyte inflammation [24]. Thus, it is evident that the pathogenesis of DIC is closely related to the inhibition of the Nrf2 signalling pathway, and therefore targeted activation of the Nrf2 signalling pathway is an important therapeutic strategy for DIC.…”
Section: Nrf2 Signalling Pathwaymentioning
confidence: 99%
“…As stated in the section on oxidative stress, the phosphorylated PI3K/AKT signaling pathway plays a crucial role in enabling the separation of Nrf2 from Keap1 in order to complete nuclear translocation. In a recent study, doxorubicin was discovered to greatly enhance the expression of Caspase-3 and BCL-2 associated X (Bax), while decreasing the expression of B cell lymphoma-2 (Bcl-2) in cardiomyocytes, indicating that doxorubicin can really alter apoptosis in cardiomyocytes [ 120 ]. Further experiments revealed that doxorubicin decreased the expression of Nrf2 and its downstream HO-1, glutathione cysteine ligase modulatory subunit (GCLM), and p-AKT, and that pharmacological intervention reversed the alterations of these factors, and that the expression levels of Nrf2 and its downstream indicators were once again reversed after AKT inhibition.…”
Section: The Role Of Nrf2 In Doxorubicin-induced Cardiotoxicitymentioning
confidence: 99%